1998
DOI: 10.1016/s0042-6989(98)00091-1
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic transparency: a test for binocular vision's disambiguating power1A part of this study was reported at the 19th European Conference on visual perception, Strasbourg 1996.1

Abstract: It has been suggested that to resolve ambiguities implicit in binocular perception of complex visual scenes, the brain adopts a continuity constraint assuming that disparities change smoothly with eccentricity. Stereoscopic transparency is characterized by abrupt changes of binocular disparity across retinal locations. The focus of the present study is how the brain uses the continuity constraint in the perception of stereoscopic transparency despite the presence of abrupt disparity changes. Observers viewed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Thus stereo-depth information is taken into account when estimating density, in line with studies on numerosity (Aida et al, 2013;Aida et al, 2015;Schütz, 2012). Along with the findings that density affects depth perception and depth-plane segmentation (Akerstrom & Todd, 1988;Buckthought & Wu, 2017;Gepshtein & Cooperman, 1998;Tsirlin et al, 2008;Tsirlin et al, 2012), density and depth processes appear to have a mutual influence.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Thus stereo-depth information is taken into account when estimating density, in line with studies on numerosity (Aida et al, 2013;Aida et al, 2015;Schütz, 2012). Along with the findings that density affects depth perception and depth-plane segmentation (Akerstrom & Todd, 1988;Buckthought & Wu, 2017;Gepshtein & Cooperman, 1998;Tsirlin et al, 2008;Tsirlin et al, 2012), density and depth processes appear to have a mutual influence.…”
Section: Discussionmentioning
confidence: 56%
“…the influence of density on depth) may provide some hints. Several studies have shown that the perception of random element, transparent surfaces defined by either stereo-depth or motion parallax is impaired at high element densities (Akerstrom & Todd, 1988;Buckthought & Wu, 2017;Gepshtein & Cooperman, 1998;Tsirlin, Allison, & Wilcox, 2008). One explanation of this finding is that increasing density will increase the ''correspondence problem'' (Tsirlin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1 , 3 . One may think that the depth reduction can be due to incorrect matches (often called ghost images or false projection), which are assumed to obstruct the visual system from finding correct matches; an increase in dot density could deteriorate stereopsis 23 , 24 . In the present study, however, we kept the number of elements in each eye constant; the total density of elements of the 2-, 3-, and 4-POTS configurations and the total number of correct matching and incorrect matching dots were the same among the three POTS.…”
Section: Discussionmentioning
confidence: 99%
“…Discussions of the strengths and weaknesses of those approaches have received considerable attention over the years (e.g. 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%